Violence in juvenile dating relationships: Self-reported prevalence and attitudes in portuguese sample - Caridade, Sónia (2019)
The objective of this study was to determine the prevalence of physical and emotional abuse in Portuguese juvenile dating relationships and to investigate attitudes about these forms of violence. A sample of 4,667 participants, aged 13 to 29 years, completed two questionnaires, one behavioral and one attitudinal. At least one act of abuse perpetrated by a dating partner during the previous year was reported by 25.4% of participants (13.4% reported to have been victims of physical abuse and 19.5% of emotional abuse). Abuse of a partner was reported by 30.6% of participants; at least one act of physical abuse was reported by 18.1% and of emotional abuse by 22.4%. The attitudinal data revealed, however, a general disapproval of violence use. Violence support was higher among males, participants with lower educational and social status and those who had never been involved in a dating relationship. Women reported more acts of partner abuse than males; no gender differences were found regarding self-reported victimization. Both perpetration and victimization were reported more by older students. Although university students tend to report more acts of general and emotional abuse against their partners, students from professional schools are more represented among both perpetrators and victims of physical and severe violence. The best predictors of violence were educational status and attitudes toward partner.